Management Waste management in Makassar city - Hasmidar Hasmidar (Brilliant International Journal Of Management And Tourism, 2023)
City Makassar's garbage problem has gotten worse Which, as of right now, cannot be handled effectively. It has been established that Makassar city streets continue to generate a significant amount of rubbish. This study intends to evaluate how Makassar City Regional Regulation Number 22 of 2018 concerning Management Rubbish in City Makassar was implemented and managed. method analysis This is a descriptive qualitative essay that employs Van Metter Van Horn's model and a critical systemic thinking method. The results demonstrate that the goals of Makassar City Regional Regulation Number 22 of 2018 concerning good waste management, budgetary restrictions as well as number efficiency existing facilities have not been met to support waste management, and there is still uncertainty in the authority distribution between stakeholders with regard to the provision of infrastructure for waste management, management systems for rubbish, and the implementation of policy management for rubbish in C. Not yet held in an ideal way, there are communication barriers that are not enough ideal and lack of public awareness. Difference analysis This is in line with earlier research on garbage management in Makassar City's scope, discussion, implementation, and policy. In addition to addressing the implementation of management policies, this study Waste also offers a different approach that the government can utilise as a guide or suggestion for more effective and efficient waste management in Makassar City.